United against cancer: prevention to end-of-life care—highlights from the Uganda Cancer Institute–Palliative Care Association of Uganda Joint International Conference on Cancer and Palliative Care and the 7th Palliative Care Conference, 24–25 August 2017, Kampala, Uganda - Downing, Julia; Ddungu, Henry; Kiyange, Fatia; Batuli, Mwazi; Kafeero, James; Kebirungi, Harriet; Kiwanuka, Rose; Mugisha, Noleb; Mwebesa, Eddie; Mwesiga, Mark; Namukwaya, Elizabeth; Niyonzima, Nixon; et al. (Ecancermedicalscience, 2017)
The Uganda Cancer Institute (UCI) and the Palliative Care Association of Uganda (PCAU) jointly hosted an international conference oncancer and palliative care in August 2017 in Kampala, Uganda. At the heart of the conference rested a common commitment to see patientcare improved across Uganda and the region. The theme – United Against Cancer: Prevention to End-of-Life Care – reflected this jointvision and the drive to remember that cancer care should include prevention, early diagnosis and screening, treatment, rehabilitation andpalliative care. The conference brought together 451 delegates from 17 countries. The key themes of the conference included: the importanceof the World Health Assembly Resolutions on Palliative Care (2014) and cancer care (2017); the need to develop a National CancerControl Programme; strategies for effective cancer diagnosis and treatment in low- and middle-income countries; advocacy, human rightsand access to essential medicines, including access to opioids and nurse prescribing; paediatric care; leadership and commitment; collaboration;resources (financial and human), the recognition that palliative care is not limited to cancer care and the importance of learningfrom each other. The conference also gave the opportunity to celebrate the 50th Anniversary of the UCI, with a celebration dinner attended by the Minister of Health and the US Ambassador. Participants reported that the conference was a forum that updated them in all aspects of cancer and palliative care, which challenged their knowledge, and was enlightening in terms of current treatment options for individuals with cancer. The benefits of having a joint conference were recognized, allowing for further networking between cancer and palliative care organizations. This conference, highlighting many developments in cancer and palliative care, served as a unique opportunity to bring people together and unite them in developing cancer and palliative care
Keywords: Cancer care; Palliative care; Uganda; Policy; Integration; Education; Research; Paediatrics; East Africa